IMPLEMENTASI TEKNOLOGI VIRTUAL DALAM VISUALISASI PENGENALAN KAMPUS MENGGUNAKAN WEBVR - Yuliana Yuliana (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2022)
One of the developments from this information is Virtual Reality (VR), a Virtual Web Technology that allows users to interact through an environment on the internet that has been simulated by a computer so that users feel they are in a virtual world. VR technology is becoming the top choice because of how it conveys messages to the environment to attract users.The purpose of this research is to be able to produce virtual web technology-based campus introduction visualizations with website results/output for campus buildings as well as immersive spatial displays and dynamic information. The research began by carrying out the 3D modeling stage using the help of Photoshop, marzipano, 3DVista tools (photos, sketches and 3D objects on one of the campus buildings. The campus building used is the Rectorate Building. Lecture building, Auditorium building. Then the system development is carried out by building data and the room is stored in a database and coded using the PHP programming language. The results of process observations during design, analysis and implementation produce a visualization WebVR Application by displaying information in the form of object, image and video formats. Virtual web technology can provide information related to the environment, campus buildings.